2021
DOI: 10.3390/w13040432
|View full text |Cite
|
Sign up to set email alerts
|

Using Multi-Factor Analysis to Predict Urban Flood Depth Based on Naive Bayes

Abstract: With global warming, the number of extreme weather events will increase. This scenario, combined with accelerating urbanization, increases the likelihood of urban flooding. Therefore, it is necessary to predict the characteristics of flooded areas caused by rainstorms, especially the flood depth. We applied the Naive Bayes theory to construct a model (NB model) to predict urban flood depth here in Zhengzhou. The model used 11 factors that affect the extent of flooding—rainfall, duration of rainfall, peak rainf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 31 publications
(33 reference statements)
0
5
0
Order By: Relevance
“…However, there is a constraint and a disadvantage to the findings of the analysis of FS using a stand-alone approach [19]. Owing to inadequate datasets, stand-alone models frequently fail to identify the best-fit function in the hypothesis space or the actual probability of the subset [100]. As a result, hybrid or ensemble modeling is used to predict the FS region accurately [3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is a constraint and a disadvantage to the findings of the analysis of FS using a stand-alone approach [19]. Owing to inadequate datasets, stand-alone models frequently fail to identify the best-fit function in the hypothesis space or the actual probability of the subset [100]. As a result, hybrid or ensemble modeling is used to predict the FS region accurately [3].…”
Section: Discussionmentioning
confidence: 99%
“…Of the classical machine learning algorithms, one of the few that is based on probability theory is naïve Bayes. Its performance comparable to that of neural networks and learning based on decision trees in some domains [100]. It is a special instance of Bayesian networks in which one node is an attribute node, and the others are feature nodes that are assumed to be independent of one another.…”
Section: Naïve Bayes (Nb)mentioning
confidence: 99%
“…For example, in medicine for the detection of cerebral infarction [29], or for coronary heart disease, breast cancer and diabetes [15]. Research in many other fields can be found too; in [36], for predicting water floods, or in [23], for earthquake predictions. Another interesting study is presented in [18], where they propose an automatic bridge crack recognition tool based on CNN and NB.…”
Section: Related Workmentioning
confidence: 99%
“…According to [6], in creating a spatial database, the data describing the factors that cause flooding include topography, geology, soil [7]. According to [8], modeling uses 11 factors that affect flood levels, namely rainfall, rainfall duration, peak rainfall, the proportion of roads, forests, grasslands, water bodies and buildings, permeability, catchment area, and slope. These factors are the hydrological review factors of an area.…”
Section: Introductionmentioning
confidence: 99%